Patients' experiences across the trajectory of atrial fibrillation: A qualitative systematic review - Jie Wang; Shenxinyu Liu; Zhipeng Bao; Min Gao; Yuanyuan Peng; Yangxi Huang; Tianxi Yu; Lin Wang; Guozhen Sun (Wiley, 2022)
Abstract Aim This study aimed to synthesize qualitative evidence on experiences of patients with atrial fibrillation (AF) during the course of diagnosis and treatment. We addressed three main questions: (a) What were the experiences of patients with AF during the course of diagnosis and treatment? (b) How did they respond to and cope with the disease? (c) What were the requirements during disease management? Design In this study, qualitative evidence synthesis was performed using the Thomas and Harden method. Data Sources Electronic databases, including PubMed, the Cochrane Library, Embase, Web of Science, Cumulative Index to Nursing and Allied Health Literature, the China Biomedical Database, the WanFang Database, Chinese National Knowledge Infrastructure and VIP, were searched. The databases were searched from inception to August 2021. Review Methods Two researchers independently selected studies using qualitative assessment and review instruments for quality evaluation and thematic synthesis for the data analysis. Results A total of 2627 studies were identified in the initial search and 15 studies were included. Five analytical themes were generated: 'Diagnosing AF'; 'The impact of AF on the patients'; 'Self‐reorientation in the therapeutic process'; 'Living with AF and QoL'; and 'External support to facilitate coping strategies.' Conclusions Our findings point out unique experiences of patients across the trajectory of AF related to delayed diagnosis, feelings of nonsupport, disappointment of repeated treatment failure and multiple distress associated with unpredictable symptoms. Future research and clinical practice are expected to improve the quality of medical diagnosis and treatment, optimize administrative strategy and provide diverse health support for patients with AF. Impact Understanding the experiences and needs of patients with AF in the entire disease process will inform future clinical practice in AF integrated management, which would be helpful in improving the professionalism and confidence of healthcare providers. In addition, our findings have implications for improving the effectiveness of AF diagnostic and treatment services. Patient or Public Contribution This paper presents a review of previous studies and did not involve patients or the public.